2021
DOI: 10.1044/2020_ajslp-20-00245
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial Myofunctional Therapy and Myofunctional Devices Used in Speech Pathology Treatment: A Systematic Quantitative Review of the Literature

Abstract: Purpose A growing number of speech-language pathologists (SLPs) are using orofacial myofunctional therapy (OMT) and/or myofunctional devices (MDs) in the treatment of their clients. However, governing bodies suggest SLPs carefully consider the availability and quality of evidence in the utilization of these therapies in speech-language pathology treatment. The purpose of this study was to review the existing evidence for OMT and MDs used by SLPs. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…The results of Shortland and colleagues [15] systematic review reported improvements in oral hygiene, oral behaviours, and swallowing, along with breathing and speech to be associated with the use of myofunctional devices. Therefore, it would be relevant to further explore treatment dosage, utilisation, and outcomes of a myofunctional device in a population such as the elderly who make up a large proportion of those whose oral health and swallowing function may be impacted [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of Shortland and colleagues [15] systematic review reported improvements in oral hygiene, oral behaviours, and swallowing, along with breathing and speech to be associated with the use of myofunctional devices. Therefore, it would be relevant to further explore treatment dosage, utilisation, and outcomes of a myofunctional device in a population such as the elderly who make up a large proportion of those whose oral health and swallowing function may be impacted [20].…”
Section: Discussionmentioning
confidence: 99%
“…This is of concern to speech pathologists due to the impact of poor oral health on mastication, swallowing function and increased risk of aspiration. However, a recent literature review [15] found that improvements in oral hygiene, oral behaviours, and swallowing, along with breathing and speech have been found to be associated with the use of orofacial myofunctional therapy and myofunctional devices [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is of concern to speech pathologists due to the impact of poor oral health on mastication, swallowing function, and increased risk of aspiration. However, a recent literature review highlights improvement in swallowing function, oral behaviours, speech, and oral hygiene with the use of orofacial myofunctional therapy and myofunctional devices [15,16]. The positive changes in orofacial functions such as lip seal, mastication, swallowing, and nasal breathing patterns are important in maintaining good oral hygiene which is identified as being problematic in an aged care population [12].…”
mentioning
confidence: 99%
“…Despite this increase of evidence, there is limited research in speech pathology that addresses the use and outcomes of myofunctional devices in clinical practice [15]. The potential impact of improvement on orofacial function, including oral hygiene and swallowing, has already been identified with the use of myofunctional devices in literature from various health disciplines [18].…”
mentioning
confidence: 99%